Autosomal dominant inheritance of abnormalities of the hands and feet with short palpebral fissures, variable microcephaly with learning disability, and oesophageal/duodenal atresia. Issue 6 (June 1991) - Brunner, H G; Winter, R M
Abstract : We report two families with an autosomal dominant syndrome of abnormalities of the hands and feet, short palpebral fissures, and variable microcephaly with learning disability. Between a third and a quarter of cases are born with oesophageal atresia, duodenal atresia, or both. Individual patients have hypoplastic thumbs or congenital heart disease. The phenotype of the syndrome reported here is similar to that observed in 13q22-qter deletion patients. However, chromosome analysis has not detected any structural abnormality in our patients.